ECT on a world map - a narrative review of the use of electroconvulsive therapy and its frequency in the world - Wingralek, Zuzanna; Banaszek, Agnieszka; Nowak, Katarzyna; Próchnicki, Michał (Current Problems of Psychiatry, 2022)
Introduction. Since implementation, electroconvulsive therapy has remained very effective treatment in psychiatry. The aim of this study is to present the differences in its use in medical practice around the world. The range of diseases in which ECT is most commonly used and the frequency of its use in different countries were compared with special attention to the differences between highly and poorly developed countries. Material and method. Review of literature by searching PubMed and Google Scholar databases using the keywords: indications of ECT, frequency of ECT use for papers published from 1991 to 2021. Results. Among the diseases for which electroconvulsive therapy is used worldwide, major depression dominates, while in Asia and Africa this therapy is used in schizophrenia. In Latin America it is used primarily for schizophrenia and bipolar disorder. In Poland, it is used for depression, bipolar disorder, and fewer for schizophrenia. The highest rate of people treated with therapy per 100,000 population is found in countries such as the USA (51), Canada (23.2-25.6), Australia (37.85), Sweden (41), Finland (23), Slovakia (29.2), Estonia (27.8) and Belgium (47). Conclusions. There is a relationship between the range of diseases most frequently treated with ECT, the frequency of use and the level of country development. In the high developed countries, ECT is used mainly in major depression, in less developed countries more frequent treatment of schizophrenia may be determined by the high cost of medications and limited availability of hospital beds. The highest rates of use of this therapy are found in more developed countries.